Quality of Life and Healthy Lifestyle of Ill Youth from Rural and Urban Areas - Duda, Marlena (Journal of Education, Technology and Computer Science, 2021)
The paper deals with the differences between the perceived quality of life and declared lifestyle of the youth suffering from chronic diseases, the said differences being important from the point of view of both social and medical sciences. This issue has not been sufficiently analysed yet, especially, its socio-demographic aspects as a cause for health inequalities. Hence, the aim of this paper is to present the differences between urban and rural areas in respect of quality of life and health-related lifestyles.